Specific ADAM10 inhibitors localize in exosome-like vesicles released by Hodgkin lymphoma and stromal cells and prevent sheddase activity carried to bystander cells. (4th May 2018) - Tosetti, Francesca; Venè, Roberta; Camodeca, Caterina; Nuti, Elisa; Rossello, Armando; D'Arrigo, Cristina; Galante, Denise; Ferrari, Nicoletta; Poggi, Alessandro; Zocchi, Maria Raffaella
ABSTRACT: Shedding of ADAM10 substrates, like TNFα, MICA or CD30, is reported to affect both anti-tumor immune response and antibody-drug-conjugate (ADC)-based immunotherapy. Soluble forms of these molecules and ADAM10 can be carried and spread in the microenvironment by exosomes released by tumor cells. We reported new ADAM10 inhibitors able to prevent MICA shedding in Hodgkin lymphoma (HL), leading to recognition of HL cells by cytotoxic lymphocytes. In this paper, we show that the mature bioactive form of ADAM10 is released in exosome-like vesicles (ExoV) by HL cells and lymph node mesenchymal stromal cells (MSC). We demonstrate that ADAM10 inhibitors are released in ExoV by MSC or HL cells, endocytosed by bystander cells and localized in the endolysosomal compartment in HL MSC. ExoV released by HL cells can enhance MICA shedding by MSC, while ExoV from MSC induce TNFα or CD30 shedding by HL cells. Of note, ADAM10 sheddase activity carried by ExoV is prevented with the ADAM10 inhibitors LT4 and CAM29, pretreating either the ExoV-producing or the ExoV-receiving cells. In particular, both inhibitors reduce CD30 shedding maintaining the anti-tumor effects of the ADC Brentuximab-Vedotin or the anti-CD30 Iratumumab on HL cells. Thus, spreading of ADAM10 activity due to ExoV can result in the release of cytokines, like TNFα, a lymphoma growth factor, or soluble molecules, like sMICA or sCD30, that potentially interfere with host immune surveillance or immunotherapy. ADAM10 blockers can interfere with this process, allowing the development of anti-lymphoma immune response and/or efficient ADC-based or human antibody-based immunotherapy.